Marxism and Left Populism in Southern Europe Today. Issue 3 (3rd July 2019) - Bidet, Jacques
ABSTRACT: The "left populism" that is currently emerging in Southern Europe conceives of itself as anti-capitalist. But its primordial concept is no longer that of social class; it is that of "the people." In the view of this current, the social-democratic and socialist parties have for the most part been absorbed by the right, so that henceforth, a popular strategy cannot consist of "rallying the left against the right, " but only of "rallying the people against the oligarchy." We are hardly even permitted to use the concept of the "left" to denote a progressive perspective, and as the struggle for emancipation simultaneously confronts capitalism, sexism, and racism, it can no longer be supported by a traditional "party-form" such as a worker's organization, but only by a more comprehensive and flexible "movement-form." Here, an attempt will be made to define the conjuncture in which the phenomenon of "left populism" has appeared, to outline its ideological constructs, to situate it in the context of the modern class structure, and finally to draw some conclusions.